Antivenoms for the treatment of snakebite envenomings: The road ahead - Gutiérrez, José María (2011)
The parenteral administration of antivenoms is the cornerstone of snakebite envenoming therapy. Efforts are made to ensure that antivenoms of adequate efficacy and safety are available world-wide. We address the main issues to be considered for the development and manufacture of improved antivenoms. Those include: (a) A knowledge-based composition design of venom mixtures used for immunization, based on biochemical, immunological, toxicological, taxonomic, clinical and epidemiological data; (b) a careful selection and adequate management of animals used for immunization; (c) well-designed immunization protocols; (d) sound innovations in plasma fractionation protocols to improve recovery, tolerability and stability of antivenoms; (e) the use of recombinant toxins as immunogens to generate antivenoms and the synthesis of engineered antibodies to substitute for animal-derived antivenoms; (f) scientific studies of the contribution of existing manufacturing steps to the inactivation or removal of viruses and other zoonotic pathogens; (g) the introduction of novel quality control tests; (h) the development of in vitro assays in substitution of in vivo tests to assess antivenom potency; and (i) scientifically-sound pre-clinical and clinical assessments of antivenoms. These tasks demand cooperative efforts at all main stages of antivenom development and production, and need concerted international partnerships between key stakeholders.